2011
DOI: 10.5539/ijef.v3n4p202
|View full text |Cite
|
Sign up to set email alerts
|

Dividend Policy and Bank Performance in Ghana

Abstract: The main thrust of this study is to find out the relationship between dividend policy and performance of banks in Ghana. The study used panel data constructed from the financial statements of 16 commercial banks in Ghana for a period of 5 years, from 1999-2003. These financial statements were obtained from the Banking Supervision department of Bank of Ghana. STATA was used for the data analysis. From the results of the study, the average dividend paid by banks over the study period was 24.65%. Also, it is appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 16 publications
2
26
1
4
Order By: Relevance
“…For any commercial bank to adopt a policy it must be adequately capitalised to justify continuity of banking activities and hence, persistent future growth, since banks address risk by maintaining a high degree of capitalisation. A priori Expectation: It is expected from this study that 3 1    > 0 (Agyei & Marfo-Yiadom, 2011;Hamid et al, 2016;Ibrahim, 2016). There should be either a uni-directional or bi-directional causal relationship between dividend policy and banks' return.…”
Section: Estimating Techniquementioning
confidence: 80%
See 1 more Smart Citation
“…For any commercial bank to adopt a policy it must be adequately capitalised to justify continuity of banking activities and hence, persistent future growth, since banks address risk by maintaining a high degree of capitalisation. A priori Expectation: It is expected from this study that 3 1    > 0 (Agyei & Marfo-Yiadom, 2011;Hamid et al, 2016;Ibrahim, 2016). There should be either a uni-directional or bi-directional causal relationship between dividend policy and banks' return.…”
Section: Estimating Techniquementioning
confidence: 80%
“…Theories such as "a bird in the hand", the signalling hypothesis and the empirical findings of Agyei and Marfo-Yiadom (2011) and Hamid et al (2016) According to Waseem, Saleh, Shukairi, and Mahmood (2011), dividend policy is unstable in the banking sector, but there are two commonly adopted dividend policies in the banking sector: namely, the dividend payout policy and the dividend re-investment plan (Retention Policy). Hence, Performance = f (Dividend payout ratio, Retention ratio)…”
Section: Methodology: Research Design Data Nature and Sourcesmentioning
confidence: 99%
“…It reflected that an increase in the company's dividend payments would affect the decline in company performance Volume 23, Issue 3, July 2019: 403-417 | 412 | in the following year, while a decrease in the value of dividend payments will affect the performance the following year. These results contradicted those of the research conducted by Agyei & Yiadom (2011), Mai (2010, Ehikioya (2015), Fauzi & Suhadak (2015), Sukendro & Pujiharjanto (2012).…”
Section: Discussionmentioning
confidence: 55%
“…Several studies have examined the impact of dividend policy on company performance. In line with the concept of signaling theory, Ehikioya (2015), Sukendro & Pujiharjanto (2012), Agyei & Yiadom (2011), Mai (2010, Yegon, Cheruiyot, & Sang (2014) found evidence that dividend policy had a positive effect on company performance. On the other hand, Kahn et al (2016) found that dividend policy harmed company performance.…”
Section: Abstrakmentioning
confidence: 88%
See 1 more Smart Citation